RANCANG BANGUN GROUND STATION DENGAN TAMPILAN GRAPHICAL USER INTERFACE PADA WAHANA ROKET BERBASIS PROCESSING DAN MENGGUNAKAN ATMEGA 328 - Sumitra Tanaya, I Nyoman; Alit Swamardika, Ida Bagus; Care Khrisne, Duman (Jurnal SPEKTRUM; Vol 8 No 1 (2021): Jurnal SPEKTRUMDO - 10.24843/SPEKTRUM.2021.v08.i01.p6, 2021)
The design of the Ground Station with a Graphical User Interface display on a Processingbased rocket vehicle and using the ATmega328 is designed to be able to assist in monitoring the environment of the rocket vehicle on the Ground Station with a Graphical User Interface display. The monitored environmental conditions include the Altitude parameter (Meter above sea level) which is detected using an Altimeter, Attitude Indicator (the position of the rocket which includes the value of the rotation angle of the Pitch, Roll, and Yaw), the position of the vehicle according to the longitude value and latitude detected by GPS (Geographical Positioning System), pointer display on each latitude and longitude point value in the Geographic Information System, Heading Indicator and real-time log data. GS can display data using an IC (Integrated Circuit) which has been integrated with an accelerometer, gyro, GPS sensors, and a communication module on a Microcontroller that can be placed on a rocket vehicle so that the IC can be called a rocket module. The rocket module is then connected to communicate with the GS using the 2.4 GHz XBee. The results of this research indicate that the GUI can display the Pitch and Roll value angles of 32.75o and 4.15o which are implemented with the attitude indicator display movement, get a Yaw angle value of 132.23o, can display an Altimeter with a ride height of 79 meters above sea level, followed by real-time log data display and GIS as a map display containing points for each change in latitude and longitude.